Clinical characteristics and outcomes of patients with COVID‐19 and psoriasis. Issue 12 (31st August 2022) - Meng, Yu; Zeng, Furong; Sun, Huiyan; Li, Yayun; Chen, Xiang; Deng, Guangtong
Abstract: To summarize the clinical characteristics and explore the role of treatment types in outcomes among psoriasis patients with coronavirus disease 2019 (COVID‐19). The principal summary measures were pooled prevalence and risk ratio (RR) with 95% confidential interval (CI). R statistic software was used for all the analysis. A total of 19 studies including 4073 psoriasis patients with COVID‐19 were eligible for the meta‐analysis. The overall hospitalization rate is about 20.2% (95% CI: 12.7%–28.7%), and changed to be 18.0% (95% CI: 9.9%–27.6%) or 14.1% (95% CI: 5.9%–24.6%) after systemic or biologic treatment. Moreover, the overall fatality rate is 1.5% (95% CI: 0.4%–3.0%), and turned to be 0.7% (95% CI: 0%–2.0%) or 0.5% (95% CI: 0%–2.2%) after systemic or biologic therapy. Notably, a lower hospitalization RR was found in patients receiving biologic therapy than those receiving other treatments (RR = 0.62, 95% CI: 0.42–0.94). The results were consistent after sensitivity analysis and trim‐and‐fill analysis. Systemic, especially biologic therapy could lessen the clinical severity in psoriasis patients with COVID‐19. Our finding will help to guide current recommendations and provide a reference for clinical decision‐making.